2003
DOI: 10.4102/hsag.v8i4.144
|View full text |Cite
|
Sign up to set email alerts
|

Muslim women’s experiences of domestic violence in the Nelson Mandela metropole: a qualitative study

Abstract: This article provides a reflection on the experiences of Muslim women with regard to domestic violence. Opsomming Hierdie artikel werp ‘n blik op Moslemvroue se ervarings van huweliksgeweld. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The participants in the study of Nordien et al (2003) found emotional abuse to be the worst kind of abuse, because the psychological effects of the abuse stayed, even after the physical abuse stopped.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants in the study of Nordien et al (2003) found emotional abuse to be the worst kind of abuse, because the psychological effects of the abuse stayed, even after the physical abuse stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors contributing to women staying in abusive relationships, could be a poor self-concept, vulnerability and manipulation by the abuser (Padayachee, 1988). Faith could contribute to women staying in abusive relationships, but it could also empower them to leave (Nordien et al, 2003). Post-separation violence is seen as an on-going effort by the abuser to continue his control over the victim and the children (Humphreys and Thiara, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations